Kitchens & baths for today & tomorrow : ideas for fabulous new kitchens & baths - Farris, Jerri. frey50 (Minneapolis, Minn. : Creative Pub. International, 2008)
"Includes insider tips, do-it-yourself instructions and inspirational photos for kitchens and bathrooms"--Provided by publisher.
Includes indexes.
Keywords: Kitchens -- Design and construction; Bathrooms -- Design and construction